Analisis Rantai Pasok Agribisnis Jagung Di Kabupaten Sigi - Erna Marliyana; Fatlina Z; Syamsuddin Syamsuddin; Suryadi Hadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to analyze the corn agribusiness supply chain in Sigi Regency, precisely in Sidondo Village. The paradigm in this study is the constructivism paradigm. A qualitative descriptive approach is used in this study. This research requires 15 informants consisting of Farmers, Fertilizer Providers, Seed Providers, Collectors, Wholesalers, Small Traders, Consumers. The data collection process was carried out by direct field interviews with informants. The data analysis method used is the Nvivo 12 Plus software. The results of this study indicate that the sweet corn agribusiness supply chain in Sidondo Village is included in the Upstream Supply Chain, Internal Supply Chain, and Downstream Supply Chain routes. The results of this study indicate that the upstream supply chain is related to the activity of providing corn seeds and the provision of corn fertilizer to corn farmers, the internal supply chain is related to the corn production process from planting to post-harvest, and the downstream supply chain is related to the distribution of crops up to the end consumers. The effectiveness and efficiency of the sweet corn agribusiness supply chain in Sidondo Village has been running well and smoothly. There is already coordination, information sharing, communication, and flexibility in corn agribusiness in Sigi District, Sidondo Village.